Variable Individual- and Population- Level Responses to Ocean Acidification - Vihtakari, Mikko; Havenhand, Jon; Renaud, Paul E.; Hendriks, Iris E. (Frontiers in Marine Science, 2016)
Population responses to marine climate change are determined by the strength of the selection pressure imposed by changing climate, the genetic variability within the population (i.e. among individuals), and phenotypic plasticity within individuals. Marine climate change research has focused primarily on population-level responses, yet it is at the level of the individual that natural selection operates. We studied individual-level responses of two bivalve species to ocean acidification (OA) at the earliest stage of the life-cycle. We measured sperm activity (swimming speed and percent motility) in the Boreal/Arctic Macoma calcarea and the temperate Mytilus galloprovincialis in response to two pCO2 levels (380 and 1000 ppm) at the ambient temperature at the collection site, i.e. 2 and 16 oC respectively. We also assessed sperm longevity under control conditions. Treatment effects on fertilization success were estimated using fertilization models. At the population level, simulated OA reduced M. galloprovincialis sperm swimming speed by 30%, percent motility by 44% and fertilization success by 43%, whereas only sperm swimming speed was significantly affected in M. calcarea. Both species showed substantial variability among individuals in response to increased pCO2. This variability was greatest in M. galloprovincialis ranging from non-significant effect to more than 73% reduction in fertilization success in response to OA, whereas M. calcarea responses varied from 8% increase in percent sperm motility to 26% reduction in swimming speed. Further, modeled fertilization success was negatively affected by simulated OA in 10 of 13 studied M. galloprovincialis males and in three of 10 M. calcarea males. We observed sperm longevities (82 h for M. calcarea and 25 h for M. galloprovincialis on average) far longer than the expected time-frame for efficient fertilization accounting for dilution of gametes. Assuming sperm activity is a heritable trait, natural selection might be a possible way for the studied populations to adapt to near-future OA.